2020
DOI: 10.4014/jmb.1907.07058
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Flavonoids from Brugmansia arborea L. Flowers

Abstract: Brugmansia arborea L. (Solanaceae), commonly known as "angel's trumpet," is widely grown in North America, Africa, Australia, and Asia. It has been mainly used for ornamental purposes as well as analgesic, anti-rheumatic, vulnerary, decongestant, and anti-spasmodic materials. B. arborea is also reported to show anti-cholinergic activity, for which many alkaloids were reported to be principally responsible. However, to the best of our knowledge, a phytochemical study of B. arborea flowers has not yet been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…The research presented in this article aimed to identify and report the potential antidiabetic effects of specie B. aurea by reducing insulin resistance in animals with the disease. Previous studies reported the anti-inflammatory ( 14 , 17 ) and anticholinergic activities ( 18 ) of this plant. However, no studies are available on its antidiabetic activity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The research presented in this article aimed to identify and report the potential antidiabetic effects of specie B. aurea by reducing insulin resistance in animals with the disease. Previous studies reported the anti-inflammatory ( 14 , 17 ) and anticholinergic activities ( 18 ) of this plant. However, no studies are available on its antidiabetic activity.…”
Section: Introductionmentioning
confidence: 82%
“…( 12 , 13 ). Flavonoids from B. aurea have previously been reported to possess antioxidant activity ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…When inflammation occurs in response to activating signals such as LPS and/or cytokines, iNOS produces NO in macrophages [13,33,36]. In addition, the level of COX-2, a pro-inflammatory enzyme, can also indicate the extent of inflammation [13,36,37]. The effect of the flavanones on iNOS and COX-2 expression was evaluated using western blot experiments.…”
Section: Inhibitory Effects Of Flavanone 1-7 On Expression Of Inos Anmentioning
confidence: 99%
“…Las plantas pertenecientes a la familia Solanaceae han sido ampliamente estudiadas desde el punto de vista farmacológico y toxicológico (Torres-Nagera et al, 2013). Algunas especies por décadas se han utilizado en la medicina tradicional basándose en el conocimiento empírico como es el caso de Brugmansia arborea "floripondio" que se cree posee propiedades analgésicas (Kim et al, 2020) en esta región la población la utiliza para tratar desde pequeños golpes hasta dolores musculares (Arteaga de García et al, 1993).…”
Section: Introductionunclassified
“…Según Caballero-Serrano et al (2019), B. arborea es ampliamente conocida en la medicina tradicional como una planta mágica, sin embargo agregan usos para tratar distintos dolores. Con base en estudios fitoquímicos (Mattioli et al, 2012;Kim et al, 2020;Algradi et al, 2021) realizados a la especie (Brugmansia arborea) se han encontrado alcaloides tales como: la atropina, hioscina, noratropina (Arteaga de García et al, 1993), hiosciamina y escopolamina (Mattioli et al, 2012), de los que en algunos casos ya se les atribuye una actividad analgésica y antiinflamatoria (Addams & Wang, 2015). Del mismo modo, Kim et al, (2020) determinaron la presencia de flavonoides como kaempferin, kaempferitrin, kaempferol, quercetin, y (+)-aromadendrin; varios de los cuales ya fueron reportados por su efecto antinociceptivo (De Melo et al, 2009, Toker et al, 2004, Almeida-Junior et al, 2020.…”
Section: Introductionunclassified